Joined - up government in Ireland: From un-strategic choices to patriotic imperatives - MacCarthaigh, Muiris; Boyle, Richard (2011)
Over the last decade, joined-up government has assumed a prominent place in the study and practice of public management. In this article, drawing on the Irish case we adopt an institutionalist approach to the issue of joining-up government and bureaucratic reform. We explore how the period of sustained and rapid economic growth in Ireland during the l990s was also characterised by a fragmentation of the public service and proliferation of agencies. Subsequently, as a consequence of the sharp contraction in public spending brought about by the global financial crisis, we find an accelerated process of public sector recentralisation, retrenchment and de-agencification. Much of this is occurring in an unplanned manner but under the generic banner of 'joining up' government. We identify the drivers behind these dynamics and how they have manifested themselves, as well as the changes to political- administrative relationships brought about by new initiatives, the power imbalances they expose, and ultimately their consequences on public service delivery. - Reproduced.
Keywords: Public administration - Ireland; Administrative reform - Ireland; Administrative reform